2009
DOI: 10.1103/physrevlett.103.118501
|View full text |Cite
|
Sign up to set email alerts
|

Triple Cascade Behavior in Quasigeostrophic and Drift Turbulence and Generation of Zonal Jets

Abstract: We study quasi-geostrophic turbulence and plasma drift turbulence within the Charney-Hasegawa-Mima (CHM) model. We focus, theoretically and using numerical simulations, on conservation of zonostrophy and on its role in the formation of the zonal jets. The zonostrophy invariant was first predicted in [1,2] in two special cases -large-scale turbulence and anisotropic turbulence. Papers [1, 2] also predicted that the three invariants, energy, enstrophy and zonostrophy, will cascade anisotropically into non-inters… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…The intermittence is characterized by the generation of a turbulence burst at time tω d0 25, as the result of the emergence of the resonant TIM with toroidal number n = 1 (note that the initial perturbed mode n = 5 has disappeared at that time). Diagrams in Figure 10 reveal the occurrence of (nonlinear) streamers with a broad spectrum (with a toroidal number of n ∼ [16][17][18][19][20][21][22][23][24], as can be seen in the plot shown at time tω d0 = 25.6. At time tω d0 = 26.8, an inverse cascade takes place leading to a dominant mode on the toroidal number n = 9, as indicated in the bottom panel in Figure 9.…”
Section: Figure 6 Continuing the Results Of Simulation Shown Inmentioning
confidence: 99%
See 2 more Smart Citations
“…The intermittence is characterized by the generation of a turbulence burst at time tω d0 25, as the result of the emergence of the resonant TIM with toroidal number n = 1 (note that the initial perturbed mode n = 5 has disappeared at that time). Diagrams in Figure 10 reveal the occurrence of (nonlinear) streamers with a broad spectrum (with a toroidal number of n ∼ [16][17][18][19][20][21][22][23][24], as can be seen in the plot shown at time tω d0 = 25.6. At time tω d0 = 26.8, an inverse cascade takes place leading to a dominant mode on the toroidal number n = 9, as indicated in the bottom panel in Figure 9.…”
Section: Figure 6 Continuing the Results Of Simulation Shown Inmentioning
confidence: 99%
“…However, this term disappears when we consider its average over α. From (19) (20) which clearly indicates that the nature of the emerged ZF is driven only by the Reynolds tensor. The similarity between the reduced Hamiltonian model for trapped ions and the CHM equation had been already pointed out in Ref.…”
Section: The Chm Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This quasi-invariant was discovered by Balk (1991) and Balk (2005) demonstrated that its conservation leads to the spectral anisotropy. The quasi-invariant was termed as zonostrophy by Nazarenko and Quinn (2009). The conservation of zonostrophy is related to the concept of resonant triad interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, zonostrophy is conserved approximately, in other words, it is conserved relatively well compared to other non-conserved quantities. Nazarenko and Quinn (2009) conducted numerical time-integrations of two-dimensional vorticity equation on a β-plane and showed that zonostrophy is conserved relatively well when the nonlinearity is sufficiently weak and that its conservation corresponds to the anisotropic upscale energy transfer. For the spherical system, quasi-invariants such as zonostrophy have not been discovered.…”
Section: Introductionmentioning
confidence: 99%